2022
DOI: 10.1002/jbt.23206
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic acid: A natural promising anticancer drug, current situation, and future perspectives

Abstract: Natural products serve as the single most productive source for the discovery of drugs and pharmaceutical leads. Among the various chemicals derived from microbes, plants, and animals, phytochemicals have emerged as potential candidates for the development of anticancer drugs due to their structural diversities, complexities, and pleiotropic effects. Herein, we discuss betulinic acid (BA), a ubiquitously distributed lupane structured pentacyclic triterpenoid, scrutinized as a promising natural agent for the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 169 publications
(279 reference statements)
0
7
0
Order By: Relevance
“…The promising use of plant triterpenoids and their derivatives in cancer treatment has also been extensively discussed in the last years, with the perspective to use these molecules as backbones for the production of semi-synthetic derivatives with improved activity and bioavailability (Oramas-Royo et al, 2010 ; Özdemir & Wimmer, 2022 ; Wang et al, 2022a ). Oleanolic, betulinic and ursolic acids are good examples of well-studied pentacyclic triterpenes that have cytotoxic activities and selectivity against multiple cancer cell lines, such as breast, cervical, and colorectal cancer, sarcomas and in vivo models (Aswathy et al, 2022 ; Chan et al, 2019 ). Although not yet fully understood, several studies have demonstrated that pentacyclic triterpenes can induce cell death by apoptosis (Chudzik et al, 2015 ; Coricovac et al, 2021 ; Hodoň et al, 2022 ; Mioc et al, 2022 ; Oprean et al, 2018 ; Ren & Kinghorn, 2019 ) or autophagy (El-Baba et al, 2021 ; Fogde et al, 2022 ; Wang et al, 2022b ).…”
Section: Resultsmentioning
confidence: 99%
“…The promising use of plant triterpenoids and their derivatives in cancer treatment has also been extensively discussed in the last years, with the perspective to use these molecules as backbones for the production of semi-synthetic derivatives with improved activity and bioavailability (Oramas-Royo et al, 2010 ; Özdemir & Wimmer, 2022 ; Wang et al, 2022a ). Oleanolic, betulinic and ursolic acids are good examples of well-studied pentacyclic triterpenes that have cytotoxic activities and selectivity against multiple cancer cell lines, such as breast, cervical, and colorectal cancer, sarcomas and in vivo models (Aswathy et al, 2022 ; Chan et al, 2019 ). Although not yet fully understood, several studies have demonstrated that pentacyclic triterpenes can induce cell death by apoptosis (Chudzik et al, 2015 ; Coricovac et al, 2021 ; Hodoň et al, 2022 ; Mioc et al, 2022 ; Oprean et al, 2018 ; Ren & Kinghorn, 2019 ) or autophagy (El-Baba et al, 2021 ; Fogde et al, 2022 ; Wang et al, 2022b ).…”
Section: Resultsmentioning
confidence: 99%
“…The slight but not statistically significant difference between the effects of the 10 and 50 mg/kg doses on serum cytokine levels may also point to a ceiling effect beyond which increased doses do not translate to proportionally greater therapeutic benefits. Moreover, pharmacokinetic factors such as absorption, distribution, metabolism, and excretion (ADME) could influence the bioavailability and, ultimately, the clinical outcomes of BA administration (Aswathy et al., 2022). The possibility of saturation kinetics at higher doses could explain the observed dose‐dependent effects.…”
Section: Discussionmentioning
confidence: 99%
“…BA can decrease the mitochondrial outer membrane potential (MOMP), increase the production of ROS, and inhibit antiapoptotic proteins while increasing the level of proapoptotic ones, thereby inducing cell apoptosis [41]. The compound can inhibit the signal transducer and activator of transcription (STAT) 3 signaling pathways, involved in differentiation, proliferation, apoptosis, metastasis formation, angiogenesis, and metabolism, and the NF-kB signaling pathway, a transcription factor commonly overexpressed in tumors that regulates processes such as cell survival, deoxyribonucleic acid (DNA) transcription, and cytokine production [41,42]. Additionally, BA has shown an ability to control cancer growth through the modulation of Sp transcription factors, inhibit DNA topoisomerase [2,10], induce autophagy [42], and inhibit the epithelial-to-mesenchymal transition (EMT) [41,43].…”
Section: Biological Properties Of Betulinic Acidmentioning
confidence: 99%